2020
DOI: 10.1177/1948550619897157
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Investigation of the Decision to Open Up a Romantic Relationship

Abstract: Consensual nonmonogamy (CNM) is an increasingly popular relationship option and a burgeoning topic within relationship science. However, retrospective designs have limited our ability to draw conclusions about the consequences of opening up a romantic relationship to other partners. In a longitudinal study, 233 individuals who were planning to engage in CNM, but who had not done so yet, were tracked over 2 months. We compared participants’ relational, sexual, and personal well-being before versus after opening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…This suggests that the driving force behind the differences between hierarchical and non-hierarchical relationships found in our study may be the lower relationship satisfaction and attachment security of non-primary (secondary and tertiary) partners. Given that relationship satisfaction with a primary partner does not appear to change after opening up a relationship (Murphy, Joel, & Muise, 2021), these findings undermine the conventional stereotype that couples become consensually non-monogamous because their primary partnership is unrewarding or unfulfilling (Conley et al, 2013).…”
Section: Overall Levels Of Relationship Satisfaction and Attachment Securitymentioning
confidence: 74%
“…This suggests that the driving force behind the differences between hierarchical and non-hierarchical relationships found in our study may be the lower relationship satisfaction and attachment security of non-primary (secondary and tertiary) partners. Given that relationship satisfaction with a primary partner does not appear to change after opening up a relationship (Murphy, Joel, & Muise, 2021), these findings undermine the conventional stereotype that couples become consensually non-monogamous because their primary partnership is unrewarding or unfulfilling (Conley et al, 2013).…”
Section: Overall Levels Of Relationship Satisfaction and Attachment Securitymentioning
confidence: 74%
“…CNM relationships are consistently devalued on a range of relationship‐relevant traits (e.g., trust, intimacy), and are perceived to be less functional and lower in quality compared to monogamous relationships (Burleigh et al, 2017; Conley et al, 2013; Grunt‐Mejer & Campbell, 2016; Hutzler et al, 2016; Moors et al, 2013; Rodrigues et al, 2017). Although current data on individuals in CNM relationships do not support these negative views (e.g., Murphy et al, 2020), one might expect monogamous individuals to anticipate engagement with CNM to be a potential threat to relational well‐being.…”
Section: Introductionmentioning
confidence: 70%
“…Individuals in CNM relationships also report that their relationship structures uniquely allow them to meet a wide variety of emotional and physical needs, to be engaged in a variety of sexual and nonsexual activities with different partners, and to experience greater personal growth and development (Conley et al, 2013; Moors et al, 2017). The only longitudinal study on record of individuals entering CNM relationships does indeed show engagement with CNM was associated with an increase in sexual satisfaction, although relationship satisfaction was not significantly changed (Murphy et al, 2020). Despite the potential benefits, one recognized cost of CNM is social stigma.…”
Section: Introductionmentioning
confidence: 99%
“…Recent qualitative research with people in CNM relationships found that the most cited benefit of CNM reported by 42% of the sample) was diversified need fulfillment (54). In fact, in a study that followed people who were considering opening up an existing relationship found that one reason people seek out additional partners is to meet needs that are unfulfilled in their current relationships (55). In this study, people who actually opened up to a CNM relationship (compared to those who did not) reported greater sexual satisfaction over the course of two months, and this was especially true if they opened up their relationship to address sexual incompatibilities with their primary partner (55).…”
Section: Broadening Our Understanding Of Need Fulfillmentmentioning
confidence: 99%
“…In fact, in a study that followed people who were considering opening up an existing relationship found that one reason people seek out additional partners is to meet needs that are unfulfilled in their current relationships (55). In this study, people who actually opened up to a CNM relationship (compared to those who did not) reported greater sexual satisfaction over the course of two months, and this was especially true if they opened up their relationship to address sexual incompatibilities with their primary partner (55). Indeed, past research has shown that relationships with primary partners are characterized by more commitment, investments, and satisfaction and greater communication than relationships with secondary partners (17; 33), and people tend to rate their primary partners as more desirable long-term partners (56).…”
Section: Broadening Our Understanding Of Need Fulfillmentmentioning
confidence: 99%